Theology of Work and the Church’s Social Mission: A Transformative Diaconal Approach to Addressing the Challenges of Street Children - Kresbinol Labobar (PT FORMOSA CENDEKIA GLOBAL, 2026)
The phenomenon of street children remains a persistent social challenge in many developing regions, including Sentani, where poverty, family disintegration, educational inequality, and limited social protection contribute to children's vulnerability and marginalization. In this context, the church is increasingly challenged to move beyond traditional charity-based ministry toward a more transformative social engagement. This study aims to examine how the theology of work can serve as a theological foundation for the church’s social mission in developing a transformative diaconal approach toward street children in Sentani, Papua. This research employs a qualitative case study design using a contextual theological approach. Data were collected through in-depth interviews, participant observation, and document analysis involving church leaders, social workers, parents, and vulnerable children within local faith communities. Data were analyzed using Thematic Analysis to identify recurring patterns and contextual meanings. The findings reveal that church social ministries in Sentani largely remain charity-oriented and have not fully integrated work theology as a framework for empowerment. However, local churches possess significant potential to become transformative agents through vocational mentoring, community-based skill development, and family empowerment initiatives. The novelty of this study lies in proposing an integrative model that connects theology of work, transformative diaconia, and indigenous community values as a contextual strategy for addressing street children in Papua.